Health economic assessment of a rabies pre-exposure prophylaxis program compared with post-exposure prophylaxis alone in high-risk age groups in the Philippines. (August 2020) - Quiambao, Beatriz; Varghese, Lijoy; Demarteau, Nadia; Sengson, Ruth Faye; Javier, Jenaline; Mukherjee, Piyali; Manio, Leah Cheryl; Preiss, Scott
Highlights: Each year, 200–300 people die from rabies in the Philippines. Vaccines can be administered after bite exposure but also in prevention. We evaluate the benefit of pre- vs post-exposure rabies vaccination. A preventive program would prevent 297 deaths over 20 years in the Philippines. It would also lead to a saving of 205 million Philippines Pesos (US$4.3 million). Abstract: Objectives: Once symptoms appear, rabies is almost always fatal and accounts for 200–300 deaths annually in the Philippines. Available rabies vaccines can be administered either in pre- exposure prophylaxis (PrEP) or post-exposure prophylaxis (PEP). After exposure, PrEP-immunized individuals require fewer doses of PEP and no rabies immunoglobulin. Methods: A static decision-tree model was developed to assess cost-effectiveness of a PrEP+PEP program vs PEP alone. Philippines-specific data for people seeking medical advice at the Research Institute for Tropical Medicine between July 2015 and June 2016 were used in the model, together with data from published literature. Results: Over a 20-year period, in a cohort of 1 million 5-year-old children in the Philippines, PrEP+PEP was expected to prevent 297 deaths compared with PEP alone. From both payer and societal perspectives, the resulting incremental cost-effectiveness ratios were 36 035 (US$759; 2016 US$ conversion) and 18 663 (US$393) Philippine Pesos (PHP) — quality-adjusted life-years gained — respectively, which are both below the willingness-to-pay threshold of PHP140 255 (US$2 953). Conclusion: These data suggest that a universal PrEP program targeting 5-year-olds would be cost-effective in the Philippines.